The attribution of work environment in explaining gender differences in long-term sickness absence: results from the prospective DREAM study. Issue 9 (25th March 2011) - Labriola, Merete; Holte, Kari Anne; Christensen, Karl Bang; Feveile, Helene; Alexanderson, Kristina; Lund, Thomas
Abstract : Objectives: To identify differences in risk of long-term sickness absence between female and male employees in Denmark and to examine to what extent differences could be explained by work environment factors. Methods: A cohort of 5026 employees (49.1% women, mean age 40.4 years; 50.9% men, mean age 40.2 years) was interviewed in 2000 regarding gender, age, family status, socio-economic position and psychosocial and physical work environment factors. The participants were followed for 18 months in order to assess their incidence of long-term sickness absence exceeding 8 consecutive weeks. Results: 298 workers (5.9%) received sickness absence compensation for 8 weeks or more. Women had an excess risk of 37% compared to men, when adjusting for age, family status and socio-economic position. Physical work environment exposures could not explain this difference, whereas differences in psychosocial work environment exposures explained 32% of the differences in risk of long-term sickness absence between men and women, causing the effect of gender to become statistically insignificant. The combined effect of physical and psychosocial factors was similar, explaining 30% of the gender difference. Conclusion: Differences in psychosocial work environments in terms of emotional demands, reward at work, management quality and role conflicts, explained roughly 30% of women's excess long-term sickness absence risk. Assuming women and men had identical working conditions would leave the larger part of the gender difference in long-term sickness absence from work unexplained.